Ecoenzymatic stoichiometry reveals widespread soil phosphorus limitation to microbial metabolism across Chinese forests - Cui, Yongxing; Bing, Haijian; Moorhead, Daryl L.; Delgado-Baquerizo, Manuel; Ye, Luping; Yu, Jialuo; Zhang, Shangpeng; Wang, Xia; Peng, Shushi; Guo, Xue; Zhu, Biao; Chen, Ji; et al. (Communications earth & environment, 2022)
Forest soils contain a large amount of organic carbon and contribute to terrestrial carbon sequestration. However, we still have a poor understanding of what nutrients limit soil microbial metabolism that drives soil carbon release across the range of boreal to tropical forests. Here we used ecoenzymatic stoichiometry methods to investigate the patterns of microbial nutrient limitations within soil profiles (organic, eluvial and parent material horizons) across 181 forest sites throughout China. Results show that, in 80% of these forests, soil microbes were limited by phosphorus availability. Microbial phosphorus limitation increased with soil depth and from boreal to tropical forests as ecosystems become wetter, warmer, more productive, and is affected by anthropogenic nitrogen deposition. We also observed an unexpected shift in the latitudinal pattern of microbial phosphorus limitation with the lowest phosphorus limitation in the warm temperate zone (41-42°N). Our study highlights the importance of soil phosphorus limitation to restoring forests and predicting their carbon sinks.